Synthesis, Characterization, and Structural Elucidation of a Novel (E)-1-(1-Phenyl-1H-pyrazol-4-yl) -N-(1-(p-tolyl)-1H-pyrazol-5-yl)methanimine - Sapkota, Kamal Raj (INTELLIGENCE Journal of Multidisciplinary Research, 2025)
(E)-1-(1-Phenyl-1H-pyrazol-4-yl)-N-(1-(p-tolyl)-1H-pyrazol-5-yl)methanimine (PPM) was synthesized by reacting 1-phenyl-1H-pyrazole-4-carbaldehyde with 1-(p-tolyl)-1H-pyrazol-5-amine in methanol, achieving a 90% yield. The elemental analysis confirmed the molecular formula, C₁₇H₁₃N₅. Structural characterization was performed using NMR, IR, UV-Vis spectroscopy, and mass spectrometry. The 1H and 13C NMR spectra identified the imine, aromatic, and pyrazole groups, verifying the molecular structure. IR analysis showed characteristic bands for C=N, aromatic C=C, NH, and CH₃ groups, consistent with the compound’s functional groups. UV-Vis spectroscopy revealed transitions at 415 nm and 325 nm, indicating an extended conjugated system. Mass spectrometry established the molecular ion at m/z 328 ([M+H]+) and identified fragmentation patterns consistent with the proposed structure. This comprehensive analysis demonstrates the successful synthesis and structural elucidation of PPM.